Polyketides from the Mangrove-Derived Endophytic Fungus Cladosporium cladosporioides - Fan-Zhong Zhang; Xiao-Ming Li; Xin Li; Sui-Qun Yang; Ling-Hong Meng; Bin-Gui Wang (Marine Drugs, 2019)
Five new polyketides, namely, 5R-hydroxyrecifeiolide (1), 5S-hydroxyrecifeiolide (2), ent-cladospolide F (3), cladospolide G (4), and cladospolide H (5), along with two known compounds (6 and 7), were isolated from the endophytic fungal strain Cladosporium cladosporioides MA-299 that was obtained from the leaves of the mangrove plant Bruguiera gymnorrhiza. The structures of these compounds were established by extensive analysis of 1D/2D NMR data, mass spectrometric data, ECDs and optical rotations, and modified Mosher’s method. The structures of 3 and 6 were confirmed by single-crystal X-ray diffraction analysis and this is the first time for reporting the crystal structures of these two compounds. All of the isolated compounds were examined for antimicrobial activities against human and aquatic bacteria and plant pathogenic fungi as well as enzymatic inhibitory activities against acetylcholinesterase. Compounds 1−4, 6, and 7 exhibited antimicrobial activity against some of the tested strains with MIC values ranging from 1.0 to 64 μg/mL, while 3 exhibited enzymatic inhibitory activity against acetylcholinesterase with the IC50 value of 40.26 μM.